The use of self-regulated learning strategies for text comprehension among ESL university student / Ismailia Ishak - Ishak, Ismailia (2007)
This study was aimed at ascertaining the degree to which ESL students use Selfregulated learning (SRL) strategies which include planning, monitoring, problem solving and evaluating. It was also aimed at assessing the degree of awareness on the part of the students based on their self-efficacy beliefs in using self-regulated strategies. The study was conducted on a group of ESL students at UiTM Sarawak for a period of a month. The investigation was carried out within 10 hours of reading class whereby the students were exposed to the four self-regulated strategies. Direct Explanation Method was used to teach students on how to use SRL strategies. The research employed a mixed method incorporating both quantitative and qualitative paradigms. The data were collected using likert-type inventories and immediate written recall protocols generated through semistructured interviews. The findings of the study reveal that the students were using the strategies frequently throughout their reading process with the exception of Evaluating strategy. The finding also shows that the students were confident of their ability in using the strategies as they reported high score on the self-rating self-efficacy scale. This study has to a certain extent provided some interesting evidence on the nature of learning the students were involved in especially as regards the use of SRL strategies. The pedagogical implication is that students should be equipped with SRL strategies through explicit instruction to help facilitate their reading comprehension process.